2020
DOI: 10.1186/s12882-020-01878-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of coexisting diabetes mellitus on clinical outcomes in patients with idiopathic membranous nephropathy: a retrospective observational study

Abstract: Background: Idiopathic membranous nephropathy (IMN) is frequently coexisted with diabetes mellitus (DM). Few researches investigate clinical outcomes in IMN patients coexisting diabetes mellitus (DM), including remission rates, renal survival and complications. Concurrent DM also pose therapeutic challenges to IMN patients due to the influence of glucocorticoids and immunosuppressant on metabolic disorders. We performed this study to investigate the impact of DM on clinical outcomes in IMN and the influence of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, the impact of DM on IMN outcomes is still elusive. Xie et al [ 21 ] compared the remission rate of patients with or without DM and concluded that even though patients with concomitant DM experienced worse renal function deterioration, no significant differences were found in remission rates between the two groups. However, another study also conducted in China, but with a larger sample size, demonstrated that concomitant DM at IMN presentation is an independent risk factor for failure to achieve CR [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of DM on IMN outcomes is still elusive. Xie et al [ 21 ] compared the remission rate of patients with or without DM and concluded that even though patients with concomitant DM experienced worse renal function deterioration, no significant differences were found in remission rates between the two groups. However, another study also conducted in China, but with a larger sample size, demonstrated that concomitant DM at IMN presentation is an independent risk factor for failure to achieve CR [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with concurrent DGS and MN on biopsy have been shown to have reduced eGFR (48.0 vs. 70.8 mL/min/1.73 m 2 ) and greater tubulointerstitial fibrosis (25.3% vs. 6.3%) compared to those with MN alone, though the same has not been seen with FSGS [ 36 ]. A study of MN from China found that both eGFR and proteinuria at the time of kidney biopsy were worse in the setting of comorbid diabetes, regardless of the presence of DGS on pathology [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of concurrent diabetes or histologic DGS has been associated with a higher rate of progression to ESKD in FSGS and MN [ 36 , 37 ]. These data align with a 2011 retrospective study by Chang et al [ 38 ] showing significantly worse cumulative renal survival in patients with DGS alone versus either NDKD alone or concomitant DGS and NDKD, suggesting potential prognostic value of biopsy in cases with clinical suspicion for NDKD.…”
Section: Discussionmentioning
confidence: 99%
“…About 20-40% of type 2 diabetes patients with microalbuminuria show overt nephropathy and about 20% will develop end-stage renal disease. [1][2][3] Diabetic nephropathy (DN) characterized by diabetic tubular damages and glomerular lesions lead to chronic kidney disease and end-stage renal failure. The risk factors in diabetes contributing to renal damages include free fatty acids, high glucose and advanced glycation end-products (AGEs).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes affects various internal organs causing neuropathy, retinopathy, myopathy, nephropathy etc. About 20–40% of type 2 diabetes patients with microalbuminuria show overt nephropathy and about 20% will develop end‐stage renal disease 1–3 . Diabetic nephropathy (DN) characterized by diabetic tubular damages and glomerular lesions lead to chronic kidney disease and end‐stage renal failure.…”
Section: Introductionmentioning
confidence: 99%